Optimalisasi Shaking Table Dalam Pencucian Bijih Timah Low Grade Di PPBT Pemali Kabupaten Bangka PT Timah Tbk - Siti Halimah Nasution1; Irvani Irvani; Alfitri Rosita (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
Tin ore processing is carried out by one of the companies namely Pemali PPBT or Tin Ore Processing Center. PPBT uses SHP feeds (leftover processing results) as material used with standard levels of ± 20% Sn. This feed will then be processed first using a water table, where the results of this process are concentrated, middling and tailing products. Concentrate with high levels while middling ranges from ± 5% Sn. This feed middling air table will be processed again with the shaking table. The increase in levels that occurred during the washing process with the shaking table only increased by 10-15%. This is because there are still many looses of minerals which are followed towards middling and tailings. Therefore it is necessary to increase the level with the trial method on setting the shaking table variables such as the washing water rate of three trials namely 4,201.7 liters / hour, 2835.3 liters / hour and 829.9 liters / hour, and on the variables slope three times the test is 2.8ᵒ, 3.8ᵒ and 4.7ᵒ. As a result of this process, the shaking table has increased levels from before processing 4-6% Sn, after being processed in the shaking table in PPBT it has increased by 10-40% Sn. Optimization of Sn and recovery levels in the right shaking table for the type in PPBT is the washing water rate of 2835.3 liters / hour with levels of 40.64% Sn and recovery of 63.6%. Slope of 3.8ᵒ with a level of 22.16% Sn and recovery of 57.0%. In combination No. 6 (3.8ᵒ and 829,9 liters / hour) with levels of 40.36% Sn and recovery 49.7%.